Reference Values for Point-of-Care Echocardiographic Measurements of Preterm Infants in China - Lu, Dan-Fang; Tong, Xiao-Mei; Liu, Yun-Feng; Zhang, Hua (Frontiers in Pediatrics, 2022)
Background Few studies have examined the reference value of the left ventricular structure and function in preterm infants. This study was designed to establish a point-of-care echocardiographic reference range of left ventricular structure and function based on different gestational age, weight, and body surface area (BSA) for preterm infants within 7 days after birth. Methods We retrospectively studied 489 patients with traditional echocardiographic data of left ventricular (LV) M-mode: LV end diastolic dimensions (LVED), LV end systolic dimension (LVES), end-diastolic interventricular septal thickness (IVSd), end diastolic LV posterior wall thickness (LVPWd), left atrial (LA) and aortic root (AO) diameters, and index of LA/AO, LV ejection fraction (LVEF), LV fractional shortening (LVFS), and pulsed wave Doppler: aortic valve flow rate (AV), peak mitral valve flow rate E(MV-E), peak mitral valve flow rate A(MV-A), and MV-E/A. The LV dimensions and the maximum blood flow velocities of the aortic valves and mitral valves according to gestational age, birth weight, and body surface area (BSA) are presented in percentiles tables. Percentile curves of aforesaid four cardiac measurements (LVED, LA diameter (LAD), MV-E, MV-E/A) using the R language Generalized Additive Models for Location, Scale and Shape (GAMLSS) method were developed according to different gestational ages and weights. Results Measurements of all cardiac dimensions and Doppler maximum velocities of AV, MV-E, and MV-E/A showed a correlation with gestational age, weight, and BSA. LVED, LAD, MV-E, and MV-E/A showed a trend of increasing values with gestational age and weight on the percentile curves. Conclusion The percentile tables and graphs of these point-of-care echocardiographic data can provide reliable reference data for Chinese neonates. Normative values are recommended as a source of reference data for the identification of potentially abnormal echocardiography.